World history patterns of interaction - Beck, Roger B.; Black, Linda; Krieger, Larry S.; Naylor, Phillip Chiviges; Shabaka, Dahia Ibo (Holt McDougal, Houghton Mifflin Harcourt, 2012)
Unit 1 : 4 million B.C-200 B.C. : Beginnings of civilization. The peopling of the world, prehistory-2500 B.C. -- Early river valley civilizations, 3500 B.C.-450 B.C. -- People and ideas on the move, 2000 B.C.-250 B.C. -- First age of empires, 1570 B.C.-200 B.C. -- Unit 2 : 2000 B.C.-A.D. 700 : New directions in government and society. Classical Greece, 2000 B.C.-300 B.C. -- Ancient Rome and early Christianity, 500 B.C.-A.D. 500 -- India and China establish empires, 400 B.C.-A.D. 550 -- African civilizations, 1500 B.C.-A.D. 700 -- The Americas : a separate world, 40,000 B.C.-A.D. 700 -- Unit 3 : 500-1500 : An age of exchange and encounter. The Muslim world, 600-1250 -- Byzantines, Russians, and Turks interact, 500-1500 -- Empires in East Asia, 600-1350 -- European Middle Ages, 500-1200 -- The formation of Western Europe, 800-1500 -- Societies and empires of Africa, 800-1500 -- Unit 4 : 500-1800 : Connecting hemispheres. People and empires in the Americas, 500-1500 -- European Renaissance and Reformation, 1300-1600 -- The Muslim world expands, 1300-1700 -- An age of explorations and isolation, 1400-1800 -- The Atlantic world, 1492-1800 -- Unit 5 : 1500-1900 : Absolutism to revolution. Absolute monarchs in Europe, 1500-1800 -- Enlightenment and revolution, 1550-1789 -- The French Revolution and Napoleon, 1789-1815 -- Nationalist revolutions sweep the West, 1789-1900 -- Unit 6 : 1700-1914 : Industrialism and the race for empire. The Industrial Revolution, 1700-1900 -- An age of democracy and progress, 1815-1914 -- The age of imperialism, 1850-1914 -- Transformations around the globe, 1800-1914 -- Unit 7 : 1900-1945 : The world at war. The Great War, 1914-1918 -- Revolution and nationalism, 1900-1939 -- Years of crisis, 1919-1939 -- World War II, 1939-1945 -- Unit 8 : 1945-Present : Perspectives on the present. Restructuring the postwar world, 1945-Present -- The colonies become new nations, 1945-Present -- Struggles for democracy, 1945-Present -- Global interdependence, 1960-Present -- References. Skillbuilder handbook -- Glossary -- Glossary in Spanish.